Identification of markers of saccharides in Polygonati rhizoma during the steaming process by MALDI-Q-TOF mass spectrometry imaging - Chuang Liu; Juan Chen; Jia Lao; You Qin; Ziling Wang; Zhenni Xie; Wei He; Can Zhong; Shuihan Zhang; Jian Jin (Food Science and Human Wellness)
Polygonati rhizoma is often used in Chinese medicine and as food. In this study, atmospheric pressure matrix-assisted laser desorption ionization and quadruple-time-of-flight (MALDI-Q-TOF) mass spectrometry techniques were applied to P. rhizoma samples from Polygonatum cyrtonema Hua species. Positive ions were mainly detected in the mass range of m/z 200–600, while negative ions were mainly observed in the mass range of m/z 100–450. A total of 263 components were identified and the spatial distribution and changes in saccharides contents during the steaming process of P. rhizoma were investigated. Monosaccharide and disaccharide exhibit a relatively uniform distribution, while the oligosaccharides were mainly found in the bast of fresh P. rhizoma. Although the contents of monosaccharide and disaccharide were increased during steaming, that of trisaccharide, tetrasaccharide, and pentasaccharide were decreased. We used the 5 saccharide types with the greatest variation in content as variables for the principal component analysis (PCA) and cluster analysis. Both PCA and cluster analysis showed that these 5 saccharides can be used as markers in the steaming process of the P. rhizoma. Present study of mass spectrometry imaging provides novel insights into the spatiotemporal accumulation patterns of saccharides in P. rhizoma, improving our understanding of the steaming process.